Comparison of individual and pooled urine samples for estimating the presence and intensity of Schistosoma haematobium infections at the population level. Issue 1 (December 2015) - Degarege, Abraham; Erko, Berhanu; Mekonnen, Zeleke; Legesse, Mengistu; Negash, Yohannes; Vercruysse, Jozef; Levecke, Bruno
Abstract Background There is a lack of cost-effective diagnostic strategies to evaluate whether mass drug administration (MDA) programmes to controlSchistosoma haematobium progress as anticipated. The purpose of this study is to provide a proof-of-principle for examination of pooled urine samples as a strategy for rapid assessment of presence and intensity ofSchistosoma haematobium infections at the population level. Methods A total of 640 urine samples were collected from 520 school-aged children (520 at baseline and 120 at follow-up) during a clinical trial that was designed to assess the efficacy of praziquantel againstSchistosoma haematobium infections in Ethiopia. Individual and pooled urine samples were screened using the filtration technique (volume of 10 ml urine) to determine the number ofS. haematobium eggs in 10 ml of urine. Samples were pooled into pools of 5 (n = 128), 10 (n = 64) and 20 (n = 32) individual samples. The sensitivity, the probability of finding at least one egg in a pooled sample when the mean urine egg count (UEC) of the corresponding individual urine samples was not zero, was calculated for each pool size. UECs of a pooled examination strategy were compared with the mean UECs of the corresponding individual samples. Results The sensitivity of a pooled examination strategy was 50.6 % for pools of 5, 68.6 % for pools of 10 and 63.3 % for pools of 20. The sensitivity of a pooled examination strategy increased as a function of increasing mean UEC of the corresponding individual urine samples. For each of the three pool sizes, there was a significant positive correlation between mean UECs of individual and those obtained in pooled samples (correlation coefficient: 0.81 – 0.93). Examination of pools of 5 provided significantly lower UECs compared to the individual examination strategy (3.9 eggs/10 ml urine versus 5.0 eggs/10 ml urine). For pools of 10 (4.4 eggs/10 ml) and 20 (4.2 eggs/10 ml), no significant difference in UECs was observed. Conclusions Examination of pooled urine samples applying urine filtration holds promise for rapid assessment of intensity ofS. haematobium infections, but may fail to detect presence of infections when endemicity is low. Further investigation is required to determine when and how pooling can be optimally implemented in monitoring of mass drug administration programmes.